2017
DOI: 10.1177/1081286517718229
|View full text |Cite
|
Sign up to set email alerts
|

A Gao beam subjected to a moving inertial point load

Abstract: A model for the dynamics of a Gao elastic or viscoelastic nonlinear beam that is subject to a horizontally moving vertical point-force is modeled and computationally studied. In particular, the behavior and vibrations of the beam as the mass is moving on it is investigated. Such problems arise naturally in transportation systems with rails. A time-marching finite element numerical algorithm for the problem is developed and implemented. Results of representative simulations are depicted and compared to the beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…There exists an extensive literature about the Timoshenko beam, see e.g., [2][3][4] and the references therein. Currently, there is a rapidly growing scientific literature about the Gao beam, see, e.g., [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. These publications deal with the modeling, mathematical analysis and computer simulations of the various aspects of the Gao beam model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There exists an extensive literature about the Timoshenko beam, see e.g., [2][3][4] and the references therein. Currently, there is a rapidly growing scientific literature about the Gao beam, see, e.g., [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. These publications deal with the modeling, mathematical analysis and computer simulations of the various aspects of the Gao beam model.…”
Section: Introductionmentioning
confidence: 99%
“…The total potentials of these beam models were non-convex, with a double-well structure, which was used in post-buckling analysis and also frictional contact problems. The analytical and numerical solutions of the model were applied to a structure subjected to a moving inertial load [14,15], representing a wheel moving on a rail. It has been shown that an inertial load significantly altered the dynamic response of the system and that omitting the nonlinear term in the differential equation led to incorrect qualitative and quantitative solutions.…”
Section: Introductionmentioning
confidence: 99%
“…This paper continues the study of the vibrations of a nonlinear Gao beam that is subjected to a moving mass [11,12] by adding a oscillating axial force. Such problems arise naturally in transportation systems such as trains or trams.…”
Section: Introductionmentioning
confidence: 86%
“…By equation (2) we know that the axial deformation could be relatively large, while the nonconvexity of the total potential shows that this nonlinear beam model can be used for studying both pre and post-buckling problems [4,30]. Recently, the Gao beam model has been generalized for many real-world applications in engineering and sciences [1,2,3,22,23,25,26,28].…”
Section: Nonconvex Problem and Canonical Duality Theorymentioning
confidence: 99%